Association between SGLT-2 inhibitors and suicide risk in type 2 diabetes and bipolar: a real-world cohort study - Chang, En-Wei; Huang, Jing-Yang; Lo, Shih-Chang; Huang, Chien-Ning; Yang, Yi-Sun; Kornelius, Edy (Frontiers in Pharmacology, 2025)
BackgroundIndividuals with bipolar disorder face a significantly elevated suicide risk, and comorbid type 2 diabetes mellitus (T2DM) further complicates their psychiatric and medical outcomes. Sodium–glucose co-transporter-2 inhibitors (SGLT-2i) have demonstrated cardiometabolic benefits in T2DM, but their impact on psychiatric outcomes remains unclear. This study investigates whether SGLT-2i use is associated with a lower risk of suicide-related events compared to dipeptidyl peptidase-4 inhibitors (DPP-4i) in individuals with bipolar disorder and T2DM.MethodsWe conducted a retrospective cohort study using the TriNetX US Collaborative Network, a large electronic health record database. Patients were included if they had bipolar disorder, were receiving active psychiatric treatment, and initiated either SGLT-2i or DPP-4i between 1 January 2015, and 30 June 2024. The primary outcome was the occurrence of suicide-related events, including suicidal ideation, suicide attempt, or intentional self-harm. Secondary outcomes included all-cause mortality, end-stage renal disease (ESRD), diabetic ketoacidosis (DKA), acute kidney injury (AKI), sepsis, genital infections, urinary tract infections (UTIs), and lower-limb amputation. Propensity score matching (1:1) was used to balance baseline characteristics. Cox proportional hazards models estimated hazard ratios (HRs) with 95% confidence intervals (CIs).ResultsThe matched cohort included 1,711 patients per group (SGLT-2i vs. DPP-4i). Over a median follow-up of 887 vs. 797 days, suicide-related events occurred in 5.1% of SGLT-2i users vs. 7.3% of DPP-4i users (HR: 0.660, 95% CI: 0.473–0.921, p = 0.0145). All-cause mortality was also lower in the SGLT-2i group (HR: 0.594, 95% CI: 0.451–0.783, p < 0.001). No significant increase in adverse events such as DKA or infections was observed.ConclusionIn this real-world cohort study, SGLT-2i use was associated with a significantly lower risk of suicide-related events and all-cause mortality compared to DPP-4i in individuals with bipolar disorder and T2DM. Subgroup analyses stratified by age, sex, race, glycemic control (HbA1c), kidney function (eGFR), and baseline lithium use revealed no evidence of increased suicide risk in any subgroup. These findings suggest that SGLT-2 inhibitors may have a neutral to potentially protective effect on suicide-related outcomes. Further prospective studies are warranted to confirm these observations and explore the underlying mechanisms.